transcription factor ATF5: role in neurodevelopment and neural tumors - Greene, Lloyd A; Lee, Hae Young; Angelastro, James M (Journal of neurochemistry, 2009)
We review recent findings regarding the properties of ATF5 and the major roles that this transcription factor plays in development of the nervous system and in survival of neural tumors. ATF5 is a widely expressed basic leucine zipper protein that has been subject to limited characterization. It is highly expressed in zones of neuroprogenitor cell proliferation. In vitro and in vivo studies indicate that it functions there to promote neuroprogenitor cell expansion and to suppress their differentiation into neurons or glia. ATF5 expression is down-regulated by trophic factors and this is required for their capacity to promote neuroprogenitor cell cycle exit and differentiation into either neurons, oligodendroglia or astrocytes. ATF5 is also highly expressed in a number of tumor types, including neural tumors such as neuroblastomas, medulloblastomas and glioblastomas. Examination of the role of ATF5 in glioblastoma cells indicates that interference with its expression or activity causes them to undergo apoptotic death. In contrast, normal astrocytes and neurons do not appear to require ATF5 for survival, indicating that it may be a selective target for treatment of glioblastomas and other neural neoplasias. Further studies are needed to identify the transcriptional targets of ATF5 and the mechanisms by which its expression is regulated in neuroprogenitors and tumors.